Pelaksanaan Praktikum Aerodrome Control Tower di Politeknik Penerbangan Indonesia Curug - Djoko Jatmoko; Pribadi Asih; Mochamad Faisal Muzaki (Politeknik Penerbangan Indonesia Curug, 2021)
This study aims to review the practical process and try to obtain an overview of the problems that arise in the practice of students guiding aircraft in the Aerodrome Control Tower lab by making observations. The research method used is a qualitative method. The research instrument uses interviews and direct observation to observe the phenomena that occur and find out the problems faced when carrying out the practice and trying to find solutions. The results showed that there were several problems found, such as the incompatibility of cadets' understanding of the material provided by each lecturer and from the guidebook itself. The need for further research for improvement in the future.